Direct oxidation esterification of methacrolein with methanol: Oxygen vacancy promotion of Zr‐doped Au/CeO2 nanorods. (4th November 2019) - Li, Yuchao; Tian, Yun; Zheng, Yanxia; Ge, Tingting; Fu, Zhongjun; Jiao, Tiantian; Wang, Ming; Huang, Haofei; Zuo, Cuncun
Abstract: A series of Zr‐doped CeO2 nanorods supported by Au nanoparticle catalysts with different morphologies were prepared for methyl methacrylate (MMA) synthesis via direct oxidation esterification of methacrolein (MAL) with methanol. Catalytic activities under mild conditions (0.3 MPa; 80°C) were evaluated in the kettle reactor. Different characterization methods, such as XRD, Raman, N2 adsorption, ICP, TEM, SEM, XPS, and H2 ‐TPR techniques, were applied to study the relationship between catalytic activity and structural characteristics, especially the form of Zr doped into the lattice of CeO2 and the promotion mechanism of selective oxidation. The influence of Au supported on Ce0.6 Zr0.4 O2 nanorods (Au/CZ‐R) was also discussed. The results exhibited that the highest catalytic activity for the oxidative esterification with a MAL conversion of 99% and a MMA selectivity of 74% was achieved. The MMA synthesis performance correlated well with the surface oxygen vacancies, in particular for the active oxygen species around the Au particles. Abstract : Morphology, catalytic mechanism, and activity performance of Au/Zr‐doped CeO2 nanorods used for MMA synthesis.